Al-Ghazali’s thought on the existence of Allah SWT in ihya’ ‘ulum al-din - Mohd Fauzi, Hamat; Mohd Hasrul, Shuhari; Muhammad Nasri, Hassan Basri (2020)
The existence of Allah SWT is among the most important topics to be considered in Islam. Islamic scholars through their works have elaborated the concept of the existence of Allah SWT so that it can be understood in the Muslim community. Among them is al-Ghazali (505H) which has been promoted by the Muslim world scientists as the mujaddid (religious reformer) for the fifth century also describes it in his masterpiece, Ihya’ ‘Ulum al-Din. This work focused on the description of a well-known Islamic scholar, al-Ghazali about the concept of the existence of Allah SWT through his book, Ihya’ ‘Ulum alDin. This qualitative study was carried out by means of content analysis to the book Ihya’ ‘Ulum al-Din to produce the output of the research. At the end of the discussion, it will be summarized some aspects of the thought of the person about the existence of Allah SWT This paper will conclude that al-Ghazali explains the existence of Allah using the passages of nature, nas and intellect. The arguments are taken from the seven Qur'anic verses and the argument by using the theory among them is the existence of something new (al-hadith) there must have been a reason (al-sabab) to make it.